Plant Physiological Aspects of Phenolic Compounds - Soto-Hernández, Marcos; García-Mateos, Rosario; Palma-Tenango, Mariana (IntechOpen, 2019)
Phenolic compounds are considered secondary metabolites within the physiology of a plant. They have different functions, such as pollination systems, sun protection, protection against pathogens and diseases, etc.Research on these compounds has increased due to the number of molecules they can include and the different biological activities they demonstrate. It is important to know the methods of extracting molecules, the biosynthesis routes, and their relationship with activities that can benefit from their consumption. Therefore, the book includes chapters that provide information on extraction and optimization techniques, biosynthetic pathways, and the identification and characterization of miRNAs involved in the regulation of their biosynthesis.